Which physical examination tests provide clinicians with the most value when examining the shoulder? Update of a systematic review with meta-analysis of individual tests. Issue 14 (7th July 2012) - Hegedus, Eric J; Goode, Adam P; Cook, Chad E; Michener, Lori; Myer, Cortney A; Myer, Daniel M; Wright, Alexis A
Abstract : Objective: To update our previously published systematic review and meta-analysis by subjecting the literature on shoulder physical examination (ShPE) to careful analysis in order to determine each tests clinical utility. Methods: This review is an update of previous work, therefore the terms in the Medline and CINAHL search strategies remained the same with the exception that the search was confined to the dates November, 2006 through to February, 2012. The previous study dates were 1966 – October, 2006. Further, the original search was expanded, without date restrictions, to include two new databases: EMBASE and the Cochrane Library. The Quality Assessment of Diagnostic Accuracy Studies, version 2 (QUADAS 2) tool was used to critique the quality of each new paper. Where appropriate, data from the prior review and this review were combined to perform meta-analysis using the updated hierarchical summary receiver operating characteristic and bivariate models. Results: Since the publication of the 2008 review, 32 additional studies were identified and critiqued. For subacromial impingement, the meta-analysis revealed that the pooled sensitivity and specificity for the Neer test was 72% and 60%, respectively, for the Hawkins-Kennedy test was 79% and 59%, respectively, and for the painful arc was 53% and 76%, respectively. Also from the meta-analysis, regarding superior labral anterior to posterior (SLAP) tears, the test with the best sensitivity (52%) was the relocation test; the test with the best specificity (95%) was Yergason's test; and the test with the best positive likelihood ratio (2.81) was the compression-rotation test. Regarding new (to this series of reviews) ShPE tests, where meta-analysis was not possible because of lack of sufficient studies or heterogeneity between studies, there are some individual tests that warrant further investigation. A highly specific test (specificity >80%, LR+ ≥ 5.0) from a low bias study is the passive distraction test for a SLAP lesion. This test may rule in a SLAP lesion when positive. A sensitive test (sensitivity >80%, LR− ≤ 0.20) of note is the shoulder shrug sign, for stiffness-related disorders (osteoarthritis and adhesive capsulitis) as well as rotator cuff tendinopathy. There are six additional tests with higher sensitivities, specificities, or both but caution is urged since all of these tests have been studied only once and more than one ShPE test (ie, active compression, biceps load II) has been introduced with great diagnostic statistics only to have further research fail to replicate the results of the original authors. The belly-off and modified belly press tests for subscapularis tendinopathy, bony apprehension test for bony instability, olecranon-manubrium percussion test for bony abnormality, passive compression for a SLAP lesion, and the lateral Jobe test for rotator cuff tear give reason for optimism since they demonstrated both high sensitivities and specificities reported in low bias studies. Finally, one additional test was studied in two separate papers. The dynamic labral shear may be sensitive for SLAP lesions but, when modified, be diagnostic of labral tears generally. Conclusion: Based on data from the original 2008 review and this update, the use of any single ShPE test to make a pathognomonic diagnosis cannot be unequivocally recommended. There exist some promising tests but their properties must be confirmed in more than one study. Combinations of ShPE tests provide better accuracy, but marginally so. These findings seem to provide support for stressing a comprehensive clinical examination including history and physical examination. However, there is a great need for large, prospective, well-designed studies that examine the diagnostic accuracy of the many aspects of the clinical examination and what combinations of these aspects are useful in differentially diagnosing pathologies of the shoulder.